Pengaruh CAR dan FDR Terhadap NPF Pada Bank Syariah yang Terdaftar Di OJK Periode 2018-2020 - Meilani Lailatul Hidayati; Nanu Hasanuh (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The economy in a country cannot be removed from the world of finance and banking. One of the problems felt by Islamic banking is non-performing financing (NPF). Furthermore, the aim of this study aims is that to determine the effect of CAR and FDR on non-performing financing (NPF). The study used a quantitative approach to Islamic commercial banks which are in Indonesia listed at the OJK. Meanwhile, the samples in this study were 3 Islamic commercial banks. The data used was quarterly financial report for the period of 2018-2020. In addition, the data processing used was SPSS version 26. The results of the study show that CAR and FDR simultaneously have no significant effect on NPF.